El reasentamiento en contexto minero. Entre la sugestión y la imposición de un nuevo orden - Hervé Huamaní, Bruno (2019)
According to the institutions (the International Financial Corporation - IFC and World Bank - WB) that regulate population resettlement and are in charge of issuing population resettlement standards, and, according to the entities that enforce these regulations, in theory, resettlements have to take place only when they are “necessary”. However, several cases has shown that what is necessary for mining projects developers differs from what is really necessary for their future neighbours - the population to be resettled. The argument of the political necessity of carrying out mining projects, almost instantaneously, annihilates any alternatives for a population to-be-displaced. This situation has revealed true power that is attributed to a mining company. By implementing a mining project, a mining company becomes the manager of the future of a community, hence of its present.Within the scope of this thesis we aimed to present the resettlement as a complex process of a “mining” government in rural context by using a broad approach applied to a Peruvian contemporary case. Our hypothesis is that a mining project builds a new social order on a territory where it settles in.Based on a case from Southern Peru, we have attempted to demonstrate in a pragmatic way the asymmetries of resources and power between a mining company and a peasant community.